Evaluasi Model Layanan Kesehatan Berbasis Komunitas Dan Teknologi Sederhana Di Daerah Pesisir Konawe Selatan - Putrawan, Agus; Mayansara , Andika; Yanti , Suci Dwi (Jurnal Sains & Kesehatan, 2025)
Indonesian coastal regions still experience significant gaps in accessing basic healthcare, particularly in remote villages. Thisstudy assesses the effectiveness of a community-based healthcare model using simple technology in two coastal villages—BunginPermai and Torokeku—in Konawe Selatan, Southeast Sulawesi. A mixed-methods approach was adopted with an exploratory andcomparative design. Quantitative data were gathered from 50 purposively selected respondents, while qualitative insights were obtained from 10 key informants through interviews and FGDs. Bungin Permai encounters severe access issues due to dependency on sea transport and limited fuel, while Torokeku, though reachable by land, lacks adequate health infrastructure. Cultural factors, including the role of local leaders and belief in shamans, influence how residents seek care. WhatsApp has been informally used for consultations but lacks structured protocols. The proposed integrated model includes tele-triage SOPs, active roles for community health cadres, health promotion efforts, and enhanced referral mechanisms. Preliminary findings suggest improved access and readiness for implementation, provided that local policies and digital literacy among healthcare workers are strengthened. The study concludes that a simple, community-centered healthcare model is both practical and replicable for improving healthcare delivery in isolated coastal areas.